(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background : One of the most important causes of neonatal death is their Low Birth Weight (less than 2500 grams). Low Birth Weight has a lot of risk factors. Low birth weight will cause physical, mental, and growth problems in the future. In respect to importance of the issue, this study aimed to determine the prevalence rate and risk factors of LBW (Low Birth Weight) in Shahroud, Iran. Methods: In a cross-sectional research, all mothers who had given birth at Bahar Hospital from 2013 to 2015 entered to the study. The information of the mothers and neonates were extracted from their records. Data were analyzed using SPSS v16 and t-test and chi-square tests. Results: 6677 mothers were enrolled in the study. The mean age of mothers was 27.20±5.43. %4.8of newborn babies had weights equal or less than 2500 grams. There was a significant relation between low birth weight and the mothers who were under 18 years, maternal addiction, and type of delivery (p value= 0.001).Also, there was a significant relationbetween Preterm labor and prevalence of Low Birth Weight, and the need to revive and hospitalization of baby in NICU (p value= 0.001). Conclusions: The infants' health is one of the main factors determining the quality of Health Services in a community. Since the rate of LBW is stillhigh, and this matter leads to a lot of problems for both family and society; preventive actions are recommended.